The Enlightenment That Failed Ideas, Revolution, and Democratic Defeat, 1748-1830 - Israel, Jonathan I. 1946- (Oxford University Press, Incorporated, 2020)
Radical and conservative Enlightenment ideologies began to break apart as the desire for a fair society clashed with questions of religion and secularization. The Enlightenment that Failed shows how ideas promoting the interest of society as a whole came to be almost defeated by ideas buttressing the interests of the privileged few.